Mercury biomagnification in a contaminated estuary food web: effects of age and trophic position using stable isotope analyses - Coelho, J. P. (2013)
The main aim of this study was to ascertain the biomagnification processes in a mercury-contaminated estuary, by clarifying the trophic web structure through stable isotope ratios. For this purpose, primary producers (seagrasses and macroalgae), invertebrates (detritivores and benthic predators) and fish were analysed for total and organic mercury and for stable carbon and nitrogen isotopic signatures. Trophic structure was accurately described by δ15N, while δ13C reflected the carbon source for each species. An increase of mercury levels was observed with trophic level, particularly for organic mercury. Results confirm mercury biomagnification to occur in this estuarine food web, especially in the organic form, both in absolute concentrations and fraction of total mercury load. Age can be considered an important variable in mercury biomagnification studies, and data adjustments to account for the different exposure periods may be necessary for a correct assessment of trophic magnification rates and ecological risk.